Performance of stone mastic asphalt incorporating Kenaf fiber - S. M. Z., Nur Syafiqah; K. A., Masri; N. E., Jasni; M., Hasan (IOP Publishing, 2021)
Stone mastic asphalt (SMA) is a type of gap-graded asphalt mixture that contain large gap between big size and small size of aggregate. These criteria tend to reduce the tensile strength of mixture. To solve this, SMA usually mixed with synthetic fiber to increase tensile strength. However, synthetic fiber is costly and rarely obtained from local supplies. Thus, the aim of this study is to utilize different percentages of natural fiber which is kenaf fiber in SMA to overcome issues related to SMA. Among the test involved were LA Abrasion, Marshall Stability, Resilient Modulus, and Dynamic Creep. From the results, it shows that the addition of 0.2% fiber contributes to lowest value of abrasion. In addition, 0.2% fiber also produces the highest density of SMA20 (Stone Mastic Asphalt Grade 20). It could be seen that 0.6% of kenaf fiber producing highest value of resilient modulus. Dynamic creep also shows a significant value for 0.2% amount of kenaf fiber. Thus, it can be concluded that the existence of fiber is capable in enhancing the performance of SMA which is evident for instance, the density. The outcome of this study also contributes to the improvement of current guideline in designing SMA mixture especially for Public Work Department of Malaysia.